PHARMACOTHERAPY OF HEART FAILURE - Vittalrao, Amberkar Mohanbabu; Thanusubramanian, Harish; Kumari K, Meena; Shaik, Arshad Basha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Abstract Heart failure is one of the major problems related to heart diseases in the modern era. Multiple comorbidities like coronary artery disease, hypertension, diabetes mellitus, anemia etc. have a great contribution in the development of heart failure.It is primarily two types systolic and diastolic heart failure. Insufficient or decreased pumping of the heart is Systolic heart failure whereas diastolic heart failure is because of lack of ability of the heart to relax or increased muscle inflexibility. The pathophysiology of heart failure is due to enhanced activity of sympathetic system, Renin Angiotensin system and structural changes in the wall of ventricle. The two definite targets of medical treatment in heart failure are: (1) Alleviation of obstructive (or) decreased output manifestations and replenishment of cardiac function. The drugs used are Frusemide, thiazides,ACE inhibitors/ARBs,Amrinone/Milrinone,Dopamine/ Dobutamine,Levosimendan,Digoxin, Hydralazine,Nitroprusside, Nitrate, Bisoprolol,Metoprolol, Nebivolol, Carvedilol (2) Prevention ofadvancementof heart failure and extension of patient survival - drugs used are Î² blockers,ACE inhibitors/ ARBs, Spironolactone andEplerenone